2017
DOI: 10.1186/s13045-017-0444-9
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor T cells: a novel therapy for solid tumors

Abstract: The chimeric antigen receptor T (CAR-T) cell therapy is a newly developed adoptive antitumor treatment. Theoretically, CAR-T cells can specifically localize and eliminate tumor cells by interacting with the tumor-associated antigens (TAAs) expressing on tumor cell surface. Current studies demonstrated that various TAAs could act as target antigens for CAR-T cells, for instance, the type III variant epidermal growth factor receptor (EGFRvIII) was considered as an ideal target for its aberrant expression on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
182
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(190 citation statements)
references
References 139 publications
1
182
0
7
Order By: Relevance
“…Early clinical trials that investigated anti-CD19 CAR-T cells in hematologic malignancies have demonstrated continued remission in patients with late stage disease [1][2][3][4][5]. CAR-T cell therapy investigating different cancer-specific targets have also shown some potential in studies of non-hematopoietic malignancies [6]. These promising results have been tempered by safety considerations, including cytokine release syndrome, neurotoxicity, and other rare and uncommon adverse events [7,8].…”
mentioning
confidence: 99%
“…Early clinical trials that investigated anti-CD19 CAR-T cells in hematologic malignancies have demonstrated continued remission in patients with late stage disease [1][2][3][4][5]. CAR-T cell therapy investigating different cancer-specific targets have also shown some potential in studies of non-hematopoietic malignancies [6]. These promising results have been tempered by safety considerations, including cytokine release syndrome, neurotoxicity, and other rare and uncommon adverse events [7,8].…”
mentioning
confidence: 99%
“…Trials are currently underway to assess the safety and efficacy of CARs in the treatment of glioblastoma, mesothelioma, and breast and ovarian carcinoma. 10,30 At the time of article preparation, several hundred active clinical trials involving CAR T-cell therapy are registered on ClinicalTrials.gov. An abundance of clinical data is thus likely to emerge in the coming months to years.…”
Section: Outcomes To Date From Car T-cell Therapymentioning
confidence: 99%
“…CD8+ CAR T-cells also exert cytotoxic effects by releasing granzyme and perforin granules, and directly stimulating apoptosis via first apoptosis signal and its ligand (fas/fas-L) and tumor necrosis factor (TNF)/TNF receptor (TNF-R) pathways that lead to tumor cell destruction. 10 Identifying suitable tumor targets is a key aspect of CAR construction. An ideal target antigen is abundantly present at the surface of tumor cells and only minimally present or absent in healthy tissue to mitigate nontumor effects.…”
mentioning
confidence: 99%
“…The past decades have witnessed the great progress in developing novel effective therapies [912], especially through diverting tumor cells from a proliferation phenotype towards a non-division state. Among the emerging therapies, cyclin-dependent kinase 4/6 (CDK4/6) inhibitors are the most attractive findings.…”
Section: Introductionmentioning
confidence: 99%